Development of a multiplex reverse transcription-PCR assay for simultaneous detection of pepper viruses - MIAO, PENG; PEI, WANG; XING-YAO, XIONG; LIANG-YING, DAI; XIN-XI, HU (The Indian Journal of Agricultural Sciences, 2018)
The aim of the present study was to establish a fourplex RT-PCR method for examining the infecting peppers to improve the efficiency of pepper virus detection, which includes Tobacco mosaic virus (TMV), Cucumber mosaic virus (CMV), Broad bean wilt virus- 2 (BBWV-2) and Potato virus Y (PVY). According to the genome sequences of TMV, CMV, BBWV-2 and PVY published by GenBank, four specific pairs of primers were designed to verify the specificity and sensitivity of detection system by simplex and multiplex RT-PCR method. In addition, using set multiplex RT-PCR method pepper plant samples of two geographic locations in China were tested and verified by simplex RT-PCR. The anticipated amplicon sizes of four primer pairs targeting TMV, CMV, BBWV-2 and PVY in both simplex and multiplex RT-PCR were 237 bp, 323 bp, 480 bp and 1057 bp, respectively, and established fourplex RT-PCR system was able to check out all sorts of viruses accurately from the pepper leaves of two geographic locations in China, which was 37.21%, 81.4%, 23.26%, and 2.33% respectively, and two or more mixed infections viruses sample accounted for 48.83% of the pepper samples. The research results show a detection technique of multiplex RT-PCR method for major peppers’ viruses, which is a rapid, sensitive and reliable method and examines CMV, TMV, PVY and BBWV-2.